Analisis Penerimaan Teknologi Terhadap Financial Technology (Fintech) Lending Dengan Mengintergrasikan TAM dan UTAUT - Ardlianti, Rana Atikah; Dewi, Ratna Sari Dewi2; Donoriyanto, Dwi Sukma (Journal of Research and Technology, 2023)
Fintech is a financial industry that creates financial services with a more efficient system, loan-based without guarantees, and intermediaries for people who are not served by conventional financial institutions. There are still many people who do not know how to use fintech correctly. This study aims to determine what variables affect the use of new technology in the form of financial technology lending with 51 respondents using the integration of two approaches, namely Theory of Acceptance Model (TAM) and The Unified Theory of Acceptance and Use of Technology (Utaut). For Utaut, add one new variable, brand and service trust. The TAM variable used is the perception of the use (PU), the perception of ease of use (PEOU), attitudes (ATT), intention to use (ITU), use (USE). While the utaut variable used is social influence (SI) and facilitation conditions (PU). Then all these variables are formed into conceptual models and are processed with SmartPLS 3.0 software. The result is to present receipts of 7 of 8 hypotheses that show the positive effects of respondents on the use of fintech lending applications. The final result of this study is that the respondent of this study has felt the ease and usefulness of the use of fintech lending applications.